The Influence of the Use of Interactive Learning Media on Students' Learning Interest - Ririn Andriani; Haifaturrahmah Haifaturrahmah; Nursina Sari (PT. Pusmedia Group Indonesia, 2025)
This study aims to analyze the effect of the use of interactive learning media on student learning outcomes at the elementary school level. This study uses the Systematic Literature Review (SLR) method, which selects various journals and previous studies to obtain findings that can be used as references in developing models or ideas in the future. The use of interactive learning media has been proven to help students understand the subject matter, because the media is able to present learning content in an interesting way, increase learning interest, and encourage active student participation in learning activities. By implementing interactive learning media in the teaching and learning process, teachers can create a more meaningful learning experience for students. The results of the study indicate that the implementation of interactive learning media in elementary schools has a significant effect on improving student learning outcomes.